A Comprehensive Review on Zygomatic Implants - Gulia, Shagun; Vigarniya, Monika Malik (Journal of Health and Allied Sciences NU, 2017)
Severely resorbed or atrophic maxilla has always posed a problem in terms of conventional implant therapy due to insufficient bone. A new approach to such situations is placing implants in the zygoma. Zygomatic implants are placed in patients with inadequate bone due to resection of the maxilla after surgery or in cases of resorbed maxilla. These are longer implants anchoraged in the zygoma, and present as an alternative to sinus augmentation or bone grafting. Being a technique sensitive procedure extreme care has to be taken during the placement of these implants to obtain promising results. This article reviews the zygomatic implants used in dentistry.
Keywords: Zygoma; Zygomatic Implants; Resorbed Maxilla; Sinus Slot Technique